(3GdEYdGe HSfJg Ydjg GdSdGes - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3eMeO Hf jRjO GdQHYj GdbRhjfj, CHh YHO Gddg, GHf eGLI,J (B273 (3g` s
(3ChdgG (B:s
(3jHJOF Hbhdg (B: (3hLOJ CQhi GHfI bjS s
(3BNQgG (B:s
(3hjfJgi HHGH eG LGA ai bQGAI GdbQBf Ydi ZjQ WgGQI s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B115s
Keywords: (3GdMOjK h GdeUWdMs